THE LIBERALIZATION OF EDUCATION UNDER THE WTO SERVICES AGREEMENT (GATS): A THREAT TO PUBLIC EDUCATIONAL POLICY? - Pereira, Ana Cristina Paulo (Revista Ética e Filosofia Política, 2018)
The liberalization of education under GATS has been in the middle of an academic battle. While the WTO’s opponents argue that it is a threat to public and good education, its supporters defend that it as a useful instrument to promote education in an organized and safe way. The main problem is to understand to what extent GATS is, in fact, a real menace to governmental power to adopt internal measures necessary to achieve policies which aim to provide education responsive to national values, culture and needs.